Reforms in the Sarawak City councils with respect to accounting and it implementation / Corina Joseph … [et al.] - Joseph, Corina; Janggu, Tamoi (2006)
This exploratory study aims to describe the reforms that have taken pace and are currently taking place in the two of the Sarawak's city councils from 1999 to 2003. The study also aims to find out the implication of IT implementation on financial performance particularly on revenue, expenditure, management of account receivable and preparation of financial statement. It can be concluded that the reforms started in both councils in 2000 mainly due to the Y2K compliance and a directive from the agencies in Sarawak. The reform would continue further as there are few modules that are still under the trial process. This is in line with the government's aspiration to become a fully electronic government in 2008. The availability of an extensive website of both councils is very much appreciated as it would enable the public to make online payment, complaints and enquiries. Thus, the quality of services provided can be improved from time to time and simultaneously helps improve the level of accountability